Environmental education with Paneleiras de Goiabeiras: Sustainable use of red mangrove bark - de Almeida, Renato; de Oliveira, Alexandre Ricardo; Senna Melo, Rosa Maria (Guará Journal, 2023)
The “Paneleiras de Goiabeiras” in Vitória, ES, are traditional artisans who use bark from the Rhizophora mangle tree to paint clay pots. However, this practice has had a negative impact on mangroves, leading to the death of the trees. The “modus operandi” of making clay pots is the first intangible cultural heritage in Brazil. In 1997, extension and environmental education activities were carried out to develop participatory ecosystem management strategies. The focal group technique was used, along with interviews with 30 artisans and 3 bark collectors, to collect data. Two assessments were conducted (March/2000 and March/2001) to monitor changes in attitudes and behaviors in the community. The bark extraction is done individually, and information about unexplored mangrove areas is not shared. After 20 months, it was found that the bark collectors continued to remove the bark, but this time, they chose mature trees with a higher concentration of tannins. The artisans also improved production planning, reducing waste, and increasing the efficiency of pot painting. It is essential to involve institutions and civil society in a dialogue on the conservation of mangroves, including the Paneleiras de Goiabeiras. Preserving the ecosystem is crucial to ensure the continuity of this cultural tradition.